PERAN MEDIA SOSIAL PADA KEPUTUSAN MEMBELI SEBAGAI LOYALITAS KONSUMEN PADA FROZEN FOOD, BEKASI - Aldi Friyatna Dira; Ananto Krisna Wardhana; Rachmat Fadly; Kurniawan Prambudi; Riris Lestiowati (Jurnal Kajian Ilmiah, 2023)
This study aims to determine the effect of social media and buying decisions as consumer loyalty to frozen food, Bekasi, the role of social media greatly influences consumers in deciding to buy a frozen food product, but how to build loyalty so that consumers remain interested and repeat purchases as a form of satisfaction of the frozen food so that producers will get high profits. This study uses a quantitative descriptive research method and uses primary data in frozen food Bekasi by taking a sample of 50 respondents in September-November 2022 multiple linear regression analysis using panel data and distributing questionnaires and interviews, after which data is processed using SPSS Analysis Version 25. The results of the study show that social media variables and buying decisions as consumer loyalty at Forozen Food Bekasi have not been fully implemented properly, that social media variables and buying decisions influence the consumer loyalty variable and have a significant positive relationship, this can be seen in the increase the role of social media to further increase buying interest and be able to increase consumer loyalty to Bekasi frozen food so that entrepreneurs need to get more attention to get maximum profits in the city of Bekasi.